Development of Lkpd Based on PBL on Integrated Thematic Learning in Class V of Elementary School - Desrinelti Desrinelti; Yalvema Miaz (STAI Hubbulwathan Duri, 2022)
This study aims to describe the validity, practicality, and effectiveness of the LKPD with the theme of Animal and Human Movement Organs through the PBL (Problem Based Learning) learning method in integrated thematic learning in fifth-grade students of State Elementary School 12 and 19 Parambahan. This research is included in the research and development (Research and Development) adapted from the Borg and Gall model. Collecting data using observations, questionnaires, written tests, and interviews and then analyzing quantitatively and qualitatively. This study resulted in a teaching material in PBL-Based LKPD on Animal and Human Movement Organ Themes, and data analysis showed that PBL-Based LKPD on Animal and Human Movement Organ Theme was practical and engaging in learning.